The influence of part-time employment towards degree student’s academic achievement at UiTM Kedah / Fatin Zulaiqha Zulkifli and Nur Hazirah Sani - Zulkifli, Fatin Zulaiqha; Sani, Nur Hazirah (2014)
A part time employment has become a normal trend among the undergraduate students’ nowadays. This trend is happening due to several reason that can be relate to the student’s personal life and needsMost of the universities in Malaysia are well aware that their student are doing part time job, in fact they are encouraging their student to have a part time job, especially for final year students. The issue toward the student who works part time is that they lost focus in their studies, and may affect their education performance. Therefore, the purpose of this study is to know the influence of part-time employment towards the degree student’s academic achievement in UiTM Kedah. The sample in this study was the degree students in nine courses in UiTM Kedah. Questionnaire was given to 159 respondents from all nine courses. The influence between amount of working hours per a week, types of part-time employment and works commitment towards the student’s academic achievement. The result of this research indicated that most of the respondents appeared to agree that works commitment and amount of working hours towards their academic achievement are not affected by these two determinants. However, the types of employment have affected their academic achievement.